Adipose-derived stem cells (ADSC) in the viability of a random pattern dorsal skin flap in rats - Suartz, Caio Vinicius (2014)
PURPOSE:To evaluate the viability of random pattern dorsal skin flaps in rats after injection of adipose-derived stem cells (ADSC).METHODS: Thirty five adult male Wistar EPM rats (weight 250-300 g) were distributed, at random, in two groups. I- Control (flap elevation with injection of saline solution) with fifteen animals and II- Experimental (flap elevation with injection of ADSC ) with fifteen animal. The ADSC were isolated from others five adult male rats. A dorsal skin flap measuring 10x4 cm was raised and a plastic barrier was placed between the flap and its bed in both groups and the injection (cells or saline solution) were perfomed immediately after the surgery. The percentage of flap necrosis was measured on the seventh postoperative day.RESULTS:The ADSC were able to replicate in our culture conditions. We also induced their adipogenic, osteogenic and chondrogenic differentiation to verify their mesenchymal stem cells potentiality in vitro. The results were statistically significant showing that the ADSC decreased the area of necrosis (p<0.05).CONCLUSIONS:The cells demonstrated adipogenic, osteogenic and chondrogenic differentiation potential in vitro. The administration of adipose-derived stem cells was effective to increase the viability of the random random pattern dorsal skin flaps in rats.